Digital Literacy: Teachers' Perceptions of Using Google Accounts in the Online Learning Process - Fatmawati Fatmawati; Noni Andriyani; Rika Ningsih (STAI Hubbulwathan Duri, 2021)
This current study explores the teacher's perspective on the usefulness of google account in the online learning process at SMAN 1 Tambang, Riau. The teachers and other school staff did not simply implement the policy of the distance learning process. The shift from face-to-face learning activities to online learning is confusing for teachers, especially senior teachers. Teachers are challenged to be able to use technology in carrying out their duties. The digital literacy of teachers is critical in the implementation of online learning. Hence, an understanding of google classroom, google meet, and google form is an influential media aid in the learning process, especially in online learning. The research method used is a survey method. The sample in this study was 46 teachers of SMAN 1 Tambang. The results showed that 46 respondents who filled out the research questionnaire, 75% stated Strongly Agree, 23% stated Agree, and 2% stated Disagree that google accounts were instrumental in the process of online learning during the Covid-19 pandemic. This result shows that the Google account is an effective learning media used in the online learning process during the Covid-19 pandemic. Therefore, teacher mastery in the use of Google accounts is part of digital literacy that needs improvement.